Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Staterpack Paket Di Telkomsel Distribution Center Gresik - Prabowo, Hengki; Sukaris, Sukaris (Jurnal Mahasiswa Manajemen, 2025)
Background - Telkomsel is the mobile network provider with the largest number of users. Telkomsel is known as a mobile operator that offers the best internet performance and provides a variety of services, one of which is the Starter Pack. However, despite the high-quality services Telkomsel offers, the company has actually seen an 18% decline in sales. Therefore, it is important to further examine whether the quality, price, and promotions of each package influence customers’ purchasing decisions. Objective - This study aims to analyze how product quality, price, and promotion influence the decision to purchase starter packs at the Telkomsel Distribution Center in Gresik. Design / Methodology / Approach - This study employed a quantitative approach with a sample of 332 respondents selected through random sampling from a customer population of 6,750 people. The sample was then analyzed using multiple linear regression. Findings - The results of the study indicate that product quality, price, and promotion have a significant influence on the decision to purchase a starter pack, both individually and collectively. Research Implication - This study confirms that the promotional efforts undertaken by Telkomsel are less effective than product quality and price; therefore, additional promotional activities—such as word-of-mouth marketing combined with door prizes—are needed to attract the attention of potential customers. Limitations - This study relied solely on respondents encountered by chance, which means that the findings are limited to respondents with different characteristics.